Comparative evaluation of the strength of adhesion by push-out bond strength tests on endodontic posts cemented with different resinous types of luting cements: An in vitro study - C. D’Amico; A. Shalini; A. Mathur; S. Sivillica; G. R.-M. La Rosa; F. Gorassini; A. G. Heboyan; L. Fiorillo; E. Pedullà (Эндодонтия Today)
INTRODUCTION. Endodontic posts play a vital role in strengthening debilitated teeth. They are luted into the radicular space using dental cements that are generally resinous. Given that the forces faced by human teeth are loading in nature and the stresses are accumulative, the bond strength of the interfaces at both the radicular dentin and luting agent and the endodontic post and the luting agent needs to be evaluated. Micro pushout bond strength (POBS) testing is done to determine these strengths. This experimental, in vitro study evaluated the adhesion strength of endodontic posts cemented with different resin-based luting agents using micro-POBS.MATERIALS AND METHODS. A total of 30 human lower incisors were selected and divided into three groups (n=10), based on the type of adhesive resin cement used for luting. Prefabricated endodontic fiber posts were inserted into the root canals of each tooth, and different resin types of cement – Estecem II, Multilink Automix, and Relyx Ultimate. were used to cement the fiber posts. The micro-POBS test measured the bond strength of the cemented pins to the root canal dentin.RESULTS. The results showed that the mean POBS of Group B was higher than that of Group A and Group C. The difference between the mean POBSs of Group A and Group C was not statistically significant (p>0.05).CONCLUSION. The resin adhesive cement used can affect the POBS of endodontic posts to root canal dentin. Clinicians should choose the appropriate resin cement for cementing endodontic posts to ensure a strong and durable bond for a good clinical prognosis.